Semantic Preference of the Word Okaa-san and Mama in Tsukuba Web Corpus: A Corpus Linguistic Analysis - Mellati Riandi Putri; Elvi Citraresmana; Inu Isnaeni Sidiq (Universitas Muhammadiyah Yogyakarta, 2023)
The use of loanwords is common in Japanese people's daily lives, such as the use of'mama' as a term for mother rather than 'okaa-san'. Using corpus linguistic analysis, this study sought to discover how okaa-san and mama are discussed in Japanese society on the internet. The mixed technique was utilized in this study, with collocate strength calculated using MI Score and subsequently categorized by using USAS semantic categories. It was discovered that the phrase okaa-san is usually used to refer to social activities, states, and processes such as the tight relationship between mother and kid. Meanwhile, the term mother is used to refer to emotional behaviors, states, and processes.